Giáo trình sức bền vật liệu - Đỗ, Kiến Quốc (Đại học Quốc gia TP.HCM, 2009)
XD004 Sức bền vật liệu BT; XD013 Sức bền vật liệu 1; XD029 Bài tập lớn Sức bền vật liệu 1; XD066 Sức bền vật liệu 2; XD067 Bài tập lớn Sức bền vật liệu 2